Vehicle recognition pipeline via DeepSort on aerial image datasets - Hanzla, Muhammad; Yusuf, Muhammad Ovais; Al Mudawi, Naif; Sadiq, Touseef; Almujally, Nouf Abdullah; Rahman, Hameedur; Alazeb, Abdulwahab; Algarni, Asaad (Frontiers in Neurorobotics, 2024)
IntroductionUnmanned aerial vehicles (UAVs) are widely used in various computer vision applications, especially in intelligent traffic monitoring, as they are agile and simplify operations while boosting efficiency. However, automating these procedures is still a significant challenge due to the difficulty of extracting foreground (vehicle) information from complex traffic scenes.MethodsThis paper presents a unique method for autonomous vehicle surveillance that uses FCM to segment aerial images. YOLOv8, which is known for its ability to detect tiny objects, is then used to detect vehicles. Additionally, a system that utilizes ORB features is employed to support vehicle recognition, assignment, and recovery across picture frames. Vehicle tracking is accomplished using DeepSORT, which elegantly combines Kalman filtering with deep learning to achieve precise results.ResultsOur proposed model demonstrates remarkable performance in vehicle identification and tracking with precision of 0.86 and 0.84 on the VEDAI and SRTID datasets, respectively, for vehicle detection.DiscussionFor vehicle tracking, the model achieves accuracies of 0.89 and 0.85 on the VEDAI and SRTID datasets, respectively.